2022
DOI: 10.1085/jgp.202213114
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive assembly of Ca2+ entry units in soleus muscle from calsequestrin knockout mice

Abstract: Calcium (Ca2+) entry units (CEUs) are junctions within the I band of the sarcomere between stacks of sarcoplasmic reticulum (SR) cisternae and extensions of the transverse (T)-tubule. CEUs contain STIM1 and Orai1 proteins, the molecular machinery of store-operated Ca2+ entry (SOCE). In extensor digitorum longus (EDL) fibers of wild-type (WT) mice, CEUs transiently assemble during acute exercise and disassemble several hours thereafter. By contrast, calsequestrin-1 (CASQ1) ablation induces a compensatory consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…But other candidates presenting similar sensitivity to heat and ROS, such as TRP Ankyrin 1, are likely to be rapidly integrated in the arsenal of Ca 2+ -permeable channels that could be probed for their therapeutic potential. In conclusion, this Symposium, which also engendered may fruitful discussions and opened the way to new collaborations among the participants (including many foreigner guests), confirmed that Italian Physiology is at the forefront of research in Ca 2+ signalling, as also proven by many other oral and poster presentations of the meeting ( Martinotti et al, 2019 ; Nesher et al, 2019 ; Badone et al, 2021 ; Lazzarini et al, 2022 ; Michelucci et al, 2022 ; Sforna et al, 2022 ; Arici et al, 2023 ; Lia et al, 2023 ).…”
Section: Discussionsupporting
confidence: 69%
“…But other candidates presenting similar sensitivity to heat and ROS, such as TRP Ankyrin 1, are likely to be rapidly integrated in the arsenal of Ca 2+ -permeable channels that could be probed for their therapeutic potential. In conclusion, this Symposium, which also engendered may fruitful discussions and opened the way to new collaborations among the participants (including many foreigner guests), confirmed that Italian Physiology is at the forefront of research in Ca 2+ signalling, as also proven by many other oral and poster presentations of the meeting ( Martinotti et al, 2019 ; Nesher et al, 2019 ; Badone et al, 2021 ; Lazzarini et al, 2022 ; Michelucci et al, 2022 ; Sforna et al, 2022 ; Arici et al, 2023 ; Lia et al, 2023 ).…”
Section: Discussionsupporting
confidence: 69%
“…total T-tubule) length and T-tubule/SR stack contact length (i.e., length of the association between T-tubule and SR stack membranes) were measured in electron micrographs of nonoverlapping regions randomly collected from muscle fibers after staining of T-tubules with potassium ferrocyanide. For each specimen, 10–15 representative fibers were analyzed, and 5 micrographs at 10,000-12,000× magnification were taken for each fiber. The incidence of T-tubule/SR stack junctions (i.e., CEUs; 100 μm2) were determined from electron micrographs of nonoverlapping regions randomly collected by counting the number of CEUs per area of section (100 μm 2 ) as described previously (42). In WT muscles, 4-5 representative fibers were analyzed, while for each of the other samples, 15-20 representative fibers were analyzed, and 5 micrographs at 10,000-12,000× magnification were taken for each fiber.…”
Section: Methodsmentioning
confidence: 99%
“…iii) The incidence of T-tubule/SR stack junctions (i.e., CEUs; 100 μm2) were determined from electron micrographs of nonoverlapping regions randomly collected by counting the number of CEUs per area of section (100 μm 2 ) as described previously (42). In WT muscles, 4-5 representative fibers were analyzed, while for each of the other samples, 15-20 representative fibers were analyzed, and 5 micrographs at 10,000-12,000× magnification were taken for each fiber.…”
Section: Quantitative Analyses Of Em Imagesmentioning
confidence: 99%
“…total T‐tubule) length and T‐tubule/SR stack contact length (i.e., length of the association between T‐tubule and SR stack membranes) were measured in electron micrographs of nonoverlapping regions randomly collected from muscle fibers after staining of T‐tubules with potassium ferrocyanide. For each specimen, 10–15 representative fibers were analyzed, and 5 micrographs at 10 000–12 000× magnification were taken for each fiber. The incidence of T‐tubule/SR stack junctions (i.e., CEUs; 100 μm 2 ) were determined from electron micrographs of nonoverlapping regions randomly collected by counting the number of CEUs per area of section (100 μm 2 ) as described previously 33 . In WT muscles, 4–5 representative fibers were analyzed, whereas for each of the other samples, 15–20 representative fibers were analyzed, and 5 micrographs at 10 000–12 000× magnification were taken for each fiber.…”
Section: Methodsmentioning
confidence: 99%